Effect of ride sharing on air quality: Evidence from Shenzhen, China - Zixuan Wang; Li Li; Jie Tang; Binglei Xie; Jiaoju Ge (Journal of Applied Economics, 2022)
Ride-sharing service has rapidly developed around the world in recent years. In this paper, we examine how ride-sharing service affects urban air pollutants based on DIDI trip and air quality data in Shenzhen, China. With the control of weather factors, we apply spatial panel models to analyse the relationship between ride-sharing service and air quality. Our research shows: 1) PM2.5, PM10, O3, NO2, and Air Quality Index (AQI) increased when DIDI order increases, while CO and SO2 are not significantly affected. 2) After analysing the air quality impact of the new policy governing ride-sharing service, the results show that most air pollutants, namely PM2.5, PM10, NO2, CO, and AQI, have significantly decreased. It implies that the ride-sharing service acts more like a substitute of public transportation than a complement as ride-sharing service has increased the number of cars on road and deteriorated the urban air quality.
Keywords: 330; air quality; DIDI; Ride-sharing service; Shenzhen